Desain Instruksional Materi Luas Permukaan Bangun Ruang Untuk Sekolah Dasar dalam Pembelajaran Jarak Jauh - Gesti Marsaulina Pakpahan; Tian Abdul Aziz (Griya Journal of Mathematics Education and Application, 2022)
This paper presents an analysis of instructional development for space geometry lessons intended for educational institutions in elementary schools, especially grade 6 in Indonesia. The selected lesson covers the topic of the surface area of a triangular prism. Learning development is carried out by conducting a needs and learner analysis as well as a specific task analysis for the selected lesson. Performance objectives and learning outcomes are discussed in detail and their alignment with each other and the overall instructional objectives.